Visual Feedback on Nonverbal Communication: A Design Exploration with Healthcare Professionals - and Hartzler, A.; Czerwinski, M.; Pratt, W.; Back, A.; Czerwinski, Mary (IEEE Pervasive Health, 2013)
Effective nonverbal communication between patients and clinicians fosters both the delivery of empathic patient-centered care and positive patient outcomes. However, few efforts to develop tools for enhancing clinician communication have focused on nonverbal aspects of the clinical encounter. We describe a novel system that both uses social signal processing technology (SSP) to capture nonverbal cues in real time and displays ambient visual feedback on control and affiliation—two primary, yet distinct dimensions of interpersonal nonverbal communication. To explore clinicians’ acceptance of and reaction to an ambient visual feedback from such a system, we conducted a Wizard-of-Oz lab study to simulate system use with 16 healthcare professionals. We further followed up with 7 of those participants and iterated on the design with a new visualization. Our results indicate that reflective visual feedback on nonverbal communication provides an acceptable way to provide clinicians with awareness of their nonverbal communication. Furthermore, we discuss implications for the design of visual feedback to encourage empathic patient-centered communication.